Provider education program on the Khorana score to promote venous thromboembolism chemoprophylaxis in patients with gynecologic cancer. Issue 4 (15th February 2022) - Apple, Annie; Prescott, Lauren; Robinson, Marc; Shultes, Kendall; Brown, Alaina
Abstract : Objective: To evaluate the efficacy of a healthcare improvement initiative to improve provider compliance with the American Society of Clinical Oncology (ASCO) guidelines for venous thromboembolism chemoprophylaxis in patients with gynecologic cancer receiving chemotherapy. Methods: A healthcare improvement initiative was implemented at our institution to improve compliance with American Society of Clinical Oncology venous thromboembolism chemoprophylaxis guidelines in patients receiving chemotherapy with a Khorana score ≥2. Baseline Khorana score and venous thromboembolism data were retrospectively collected for chemotherapy-naïve patients with gynecologic cancer initiating chemotherapy between December 2018 and November 2019. Data for the post-intervention period from December 2019 to December 2020 were captured prospectively. Primary outcome was compliance with American Society of Clinical Oncology guidelines. Secondary outcomes were incidence of venous thromboembolism and complications surrounding venous thromboembolism chemoprophylaxis. Results: We identified 62 patients in the pre-implementation cohort. Approximately half had a Khorana score of ≥2 (52%). Median Khorana score was 2 (range 1–4). None of these patients received prophylactic chemoprophylaxis. Seven (11%) of these patients were diagnosed with venous thromboembolism. Multivariate logistic regression showed increasing Khorana score was associated with increased venous thromboembolism risk (OR 4.9, p=0.01). With cut-off Khorana score of 2, there was no significant increase in venous thromboembolism. However, with a cut-off Khorana score of 3, patients were 15 times more likely to have venous thromboembolism (OR 15.2, p=0.04). In the post-intervention cohort, 22 patients were eligible for chemoprophylaxis and 11 patients were given anticoagulation (50% compliance with guidelines), with no incidence of venous thromboembolism or adverse effects of therapy noted among those receiving chemoprophylaxis. Conclusion: Notifying providers of a patient's Khorana score improves compliance with American Society of Clinical Oncology guidelines for venous thromboembolism chemoprophylaxis among chemotherapy patients.